Proactive support of labor : the challenge of normal childbirth - Reuwer, Paul; Bruinse, Hein; Franx, Arie (Cambridge : Cambridge University Press, 2015)
The right for every woman to have a'natural' birth has been recognized for many years, yet surgical interventions continue to rise and, paradoxically, complaints and the degree of litigation for disappointing labor outcomes escalate. Proactive Support of Labor enhances professional skills by providing the expertise for preventing long labors - the root-cause of traumatic birth experiences and the cesarean pandemic. Step-by-step, evidence-based guidance on expert care and support during labor is given. Emphasis is placed on pre-labor education, personal attention, and well-defined birth planning - including strict diagnoses and timely corrective measures in abnormal labor - and constant audit of all procedures and outcomes. Striking a new balance between natural birth and intervention, and invariably enhancing women's satisfaction with the childbirth experience, the fully updated revision of this groundbreaking work will be essential reading for obstetricians, midwives, nurses, and trainees. For peer and reader reviews of the first edition see: www.proactivesupportoflabor.com.
Title from publisher's bibliographic system (viewed on 13 May 2016).
Keywords: Maternal health services; Delivery, Obstetric -- methods; Natural childbirth; Obstetric Labor Complications -- prevention & control; Pregnancy Outcome